Plasma Sphingomyelin Levels Mediate the Causal Relationship Between Gut Microbiota and Myocardial Interstitial Fibrosis: A Mendelian Randomization Study - Yu, Mingjun; Huang, Xingxiao; Gao, Beibei; Huang, Jinyu (Current Molecular Medicine, 2025)
BackgroundPrior studies established associations between gut microbiota and myocardial interstitial fibrosis. Nevertheless, the causal relationships and potential intermediaries remain unknown. Thus, we employed a Mendelian randomization strategy to explore whether gut microbiota causally influence myocardial interstitial fibrosis and to assess whether plasma metabolites serve as potential intermediaries in this pathway.MethodsA two-sample Mendelian randomization approach was performed, utilizing genome-wide association studies to examine the causal relationship between gut microbiota (n= 18,340) and myocardial interstitial fibrosis (n=41,505). Additionally, an investigation was conducted to determine the potential mediation by four plasma metabolites (n=8,299) via a two-step Mendelian randomization analysis. Inverse variance weighted method was the primary method employed in Mendelian randomization, and complementary analyses were conducted alongside to enhance the robustness of the results.ResultsMendelian randomization analysis indicated suggestive associations of three microbial taxa with myocardial interstitial fibrosis. The most significant taxon was the genus Faecalibacterium (β [SE], -0.1272 [0.0347], P = 0.0002). Reverse Mendelian randomization analyses revealed no evidence of myocardial interstitial fibrosis affecting these three microbial taxa. In the two-step Mendelian randomization analysis involving four plasma metabolites, it was found that plasma sphingomyelin levels mediated the causal effects of genus Faecalibacterium on myocardial interstitial fibrosis (proportion mediated = 14.2%, 95% CI = 1.4-27.0%).ConclusionThe study validates the causality between particular gut microbial taxa and myocardial interstitial fibrosis, and suggests that plasma sphingomyelin might mediate this association. These findings offer a novel perspective on myocardial interstitial fibrosis prevention, and underscore the significance of plasma sphingomyelin in human health and disease.
Keywords: myocardial interstitial fibrosis